Nonlinear Optimal Control Theory - Berkovitz, Leonard David; Medhin, Nagash G (Boca Raton : CRC Press, 2013)
"Preface This book is an introduction to the mathematical theory of optimal control of processes governed by ordinary differential and certain types of differential equations with memory. The book is intended for students, mathematicians, and those who apply the techniques of optimal control in their research. Our intention is to give a broad, yet relatively deep, concise and coherent introduction to the subject. We have dedicated an entire chapter for examples. We have dealt with the examples pointing out the mathematical issues that one needs to address. The first six chapters can provide enough material for an introductory course in optimal control theory governed by differential equations. Chapters 3, 4, and 5 could be covered with more or less details in the mathematical issues depending on the mathematical background of the students. For students with background in functional analysis and measure theory Chapter 7 can be added. Chapter 7 is a more mathematically rigorous version of the material in Chapter 6. We have included material dealing with problems governed by integrodifferential and delay equations. We have given a unified treatment of bounded state problems governed by ordinary, integrodifferential, and delay systems. We have also added material dealing with the Hamilton-Jacobi Theory. This material sheds light on the mathematical details that accompany the material in Chapter 6"--
"A Chapman & Hall book."
Keywords: Nonlinear control theory; MATHEMATICS / Applied; MATHEMATICS / Differential Equations; TECHNOLOGY & ENGINEERING / Electrical